(untitled) (diségno, 2024)
“Space melts like sand running through one’s fingers. Time bears it away and leaves me only shapeless shreds” [Perec 1999, p. 91 translation by the author]. Architectures that have remained marks on paper stored in archives or surviving in the form of projects after their material life; monumental heritages that have disappeared due to anthropic or natural causes; spaces that are impractical or completely closed to public use; intangible heritage; altered constructions for which the original meaning has been lost. Many occasions make cultural heritage inaccessible in the broadest sense of the term, which includes physical, sensory, cognitive, geographical, and cultural aspects. [read more]